Desarrollo integral infantil en los niños (as) del establecimiento de reclusión El Pedregal (DIER) (2021)
This research was developed from a qualitative method with a hermeneutic-dialectical approach, through individual semi-structured interviews and focus groups, from a holistic, thoughtful and sensitive view of researchers in the face of the voices and realities of the ten participants; ICBF-INPEC officials, educational agent, internal support assistants and mothers deprived of liberty. Thus, it was aimed to understand how Child Development in Detention Establishments (DIER) contributes to the process of integral development of children of the El Pedregal prison, inferring that, within the prison context, the State assumes responsibility for guaranteeing the rights of children, but, the strategies that promote the pedagogical and educational processes that are carried out with mothers and families, these being influential aspects in integral development, cannot be recognized. In line with the analysis carried out, four chapters were developed; Integral Development: Superfluous, Discipline: A Pedagogical Practice, Integral Development of Children: A Regulated Discursive Practice, and Cosification of Childhoods in the DIER. Specifying the different perspectives and finding common ground that give meaning to the path drawn in the investigation, identifying the pedagogical and educational practices that are carried out in the DIER, the processes that are carried out with mothers in relation to their children, role of the educational agent and the conception that these integral development agents have built, discovering a need for harmonious and intentional processes